(untitled) (International journal of artificial intelligence, 2024)
One of the main features of modern pedagogical technologies is the wide use of didactic materials, including modern information technologies and technical tools, which are used in the field of raising a mature generation. The possibilities of using information and communication technologies in the process of teaching specific subjects are endless. Taking this into account, this article describes innovative methods of using information technologies in the organization of the educational process.